2017
DOI: 10.4315/0362-028x.jfp-16-561
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Campylobacter jejuni Isolated from Retail Chicken in Tianjin, China

Abstract: Campylobacter jejuni is an important foodborne pathogen worldwide; however, there is a lack of information on the prevalence and antibiotic-resistant profile of C. jejuni in the People's Republic of China. We determined the prevalence and characteristics of C. jejuni on the retail level in Tianjin, one of the five national central cities in China. A total of 227 samples of chicken wings, legs, and breasts were collected from supermarkets and wet markets; 42 of these samples were confirmed to be positive for Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 50 publications
3
19
1
1
Order By: Relevance
“…In this study, 60 (75%) C. jejuni isolates were found resistant to tetracycline, the results corroborate with those reported by Nguyen et al (), whereas, Ma et al, reported high rate (77.4%) of tetracycline resistance in C. jejuni isolates. C. jejuni isolates (38.75%) were found resistant to ciprofloxacin, this result was in agreement with previous reports (Gblossi Bernadette et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, 60 (75%) C. jejuni isolates were found resistant to tetracycline, the results corroborate with those reported by Nguyen et al (), whereas, Ma et al, reported high rate (77.4%) of tetracycline resistance in C. jejuni isolates. C. jejuni isolates (38.75%) were found resistant to ciprofloxacin, this result was in agreement with previous reports (Gblossi Bernadette et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…All the isolates of C. jejuni were found sensitive to chloramphenicol and this result was in accordance with Guyard‐Nicodème et al (), whereas, Ma et al, reported 19.4% resistance of C. jejuni to ciprofloxacin.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The national surveillance data from 20 provinces in China demonstrated that the prevalence and risk assessment of C. jejuni in Chicken was relatively high [27,28]. The prevalence of C. jejuni in chicken meat was reported as 13.7% (31/227) in Tianjin [29] and 17.2% (52/302) in central China [23]. Handling and consumption of chicken meat are the major risk factors for human Campylobacteriosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of 64.8 cases per 100,000 population was reported in EU countries in 2017. It was the second most common food borne illness in the USA (EFSA and ECDC, 2018;Ma et al, 2017).…”
Section: Introductionmentioning
confidence: 99%